Synthesis of Cobalt–Glycerate hierarchical structure and their conversion into hierarchical CoP nanospheres for the hydrogen evolution reaction. (25th January 2018) - Guo, Xiaosong; Liang, Jun; Wang, Liu; Feng, Zijia; Yu, Tongtong; Zhang, Zihao; Shao, Yalong; Hao, Chuncheng; Li, Guicun
Abstract: One of the effective strategies to enhance hydrogen evolution reaction (HER) performance is to increase the catalytic sites of catalyst by designing and tailoring the nanoscale morphology of the catalyst. In this work, by using solid Co-glycerate (CoG) nanospheres as sacrificial template, various CoG hierarchical structures were successfully fabricated in water/ethanol mixed solution via a solvothermal reaction. The microstructure and morphology of obtained CoG nanospheres could be simply tuned by varying the water content. After a subsequent phosphorization reaction, multi-structural CoG was converted into hierarchical CoP nanospheres with well-preserved morphology. The essential influence of water on the microstructure of CoG was discussed in detail. Owing to the ultrathin nanosheet subunits, the as-prepared CoP nanospheres exhibited high performance with overpotential of 121 mV to achieve the current densities of 10 mA cm −2, small Tafel slope of 56 mV dec −1, and good stability under acidic condition. This work could provide an effective strategy to fabricate metal phosphide electrocatalysts with delicate hierarchical nanostructure for the application of HER. Graphical abstract: Synthesis procedure of CoP nanospheres with nanosheet-constructed shells for the hydrogen evolution Reaction. Highlights: The various CoG hierarchical structures have been successfully synthesized via a two-step hydrothermal method. The multi-structural CoG can be converted into hierarchical CoP nanospheres with well-preserved morphology. The nanosheet subunits can supply more active areas and accessible catalytic sites for hydrogen evolution reaction.